The beginner's guide to self sufficiency projects for the home : grow edibles, raise animals, live off the grid & DIY - Walsh, Tracy (New Shoe Press, 2024)
"Build a self-sufficient life with projects for growing and preserving your own food, keeping animals, harnessing alternative energy, and more. Learning to do more things yourself is healthy, rewarding, and fulfilling, and it benefits the environment. Whether you live in the suburbs or have dozens of acres in the mountains, this new and affordable edition adpated from the best-selling Step-by-Step Projects for Self-Sufficiency guides your way with clear plan drawings, precise instructions, and detailed photos. Organised into categories, such as Chickens and Other Creatures, Nourishing Your Garden, Garden Projects, Food Preparation and Preservation, and Homestead Amenities, you'll discover countless ways for you to further connect your daily life to your environment"--Publisher's description.